2017
DOI: 10.1111/jcpp.12840
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal functional magnetic resonance imaging study of task control circuits and bulimic symptoms over adolescence

Abstract: These longitudinal findings suggest overengagement of task control circuits in BN adolescents, especially those most resilient to persistent illness. Such overengagement may compensate for regulatory disturbances, allowing them to regulate eating behaviors over development. Thus, task control circuits may constitute targets for early interventions that enhance self-regulatory control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Whittle et al (2013) found that psychopathology in early adolescence mediated effects of childhood maltreatment on the development of amygdala and hippocampal volumes. Another study, in adolescent females, showed that increased symptoms of bulimia nervosa predicted change over time in brain function, assessed via fMRI, during a cognitive control/conflict resolution task (a Simon task), in the inferior frontal cortex (Cyr, Fontaine, et al, 2017). However, brain function did not predict the development of bulimia symptoms.…”
Section: Evidence For Stress-generation Modelsmentioning
confidence: 99%
“…Whittle et al (2013) found that psychopathology in early adolescence mediated effects of childhood maltreatment on the development of amygdala and hippocampal volumes. Another study, in adolescent females, showed that increased symptoms of bulimia nervosa predicted change over time in brain function, assessed via fMRI, during a cognitive control/conflict resolution task (a Simon task), in the inferior frontal cortex (Cyr, Fontaine, et al, 2017). However, brain function did not predict the development of bulimia symptoms.…”
Section: Evidence For Stress-generation Modelsmentioning
confidence: 99%
“…Participants completed the Simon task (previously described). [49][50][51] Briefly, participants were presented with a leftward or rightward pointing arrow on each trial that was congruent or incongruent with its position (left or right) on the screen. They were instructed to respond as quickly and accurately as possible to the direction of the arrow by pressing a button on a response box using the index finger for left and the middle finger for right.…”
Section: Functional Magnetic Resonance Imaging Paradigmmentioning
confidence: 99%